Methodology: co-production of knowledge for ownership and sustainability - Meelad, A.; Shah, Muhammad Azeem Ali; Lautze, Jonathan F. (CAB International, 2023)
This chapter outlines the co-production process through which this book was developed. The chapter compares its approach to other efforts to generate knowledge in transboundary basin management, and points to certain comparative advantages. Four key points that motivated the book’s focus were elaborated, namely: i) new knowledge generation, ii) fostering a common perspective, iii) enhancing human development, and iv) identification of development options. The iterative process through which the book arrived at its structure, identified authors, and facilitated their joint work are also explained. Notable limitations, e.g., related to data, and challenges, e.g,, political change in Afghanistan, are acknowledged, and the nuts and bolts of chapter review and evaluation are discussed. The chapter concludes with reflection on key lessons on the co-production approach applied, such as its contribution to trust-building between experts in the two countries.